Roles of Gut Bacteriophages in the Pathogenesis and Treatment of Inflammatory Bowel Disease - Qv, Lingling; Mao, Sunbing; Li, Yongjun; Zhang, Jia; Li, Lanjuan (Frontiers in Cellular and Infection Microbiology, 2021)
Inflammatory bowel disease (IBD), including Crohn’s disease and ulcerative colitis, are chronic, relapsing intestinal inflammatory disorders. Although the molecular mechanisms governing the pathogenesis of IBD are not completely clear, the main factors are presumed to be a complex interaction between genetic predisposition, host immune response and environmental exposure, especially the intestinal microbiome. Currently, most studies have focused on the role of gut bacteria in the onset and development of IBD, whereas little attention has been paid to the enteroviruses. Among of them, viruses that infect prokaryotes, called bacteriophages (phages) occupy the majority (90%) in population. Moreover, several recent studies have reported the capability of regulating the bacterial population in the gut, and the direct and indirect influence on host immune response. The present review highlights the roles of gut phages in IBD pathogenesis and explores the potentiality of phages as a therapeutic target for IBD treatment.